Recent History of Ischaemic Heart Disease and Duodenal Ulcer in Doctors. Issue 5620 (21st September 1968) - Meade, T. W.; Arie, T. H. D.; Brewis, M.; Bond, D. J.; Morris, J. N.
Abstract : Data are presented on the incidence of ischaemic (coronary) heart disease and duodenal ulcer among the several thousand male medical practitioners aged 35–64 holding immediate sickness benefit policies with the Medical Sickness Annuity and Life Assurance Society Limited. Three periods are considered: 1947–50, 1957–60, and 1961–5. The incidence of first clinical episodes of ischaemic heart disease in the doctors altered little between 1947–50 and 1957–60 but increased in 1961–5. Comparison of the late 1940s with the early 1960s shows a 60% rise of incidence at ages 45–54 but little change at other ages. Cases first presenting as "sudden" death increased between 1947–50 and 1961–5 by 111% at 45–54, and again changed little at 55–64. In two other occupational groups that have been studied—bus conductors and insurance salesmen—the increase of incidence was greater than for the doctors at 45–54 and it occurred also over 55 years of age. The increase from 1947–50 to 1961–5 in mortality during all episodes of ischaemic heart disease was the same in the doctors as in the male population of England and Wales at 45–54, but at 55–64 it was less. The results in the doctors are not due to alterations over the period in length of sickness absence, or underwriting policy, or of the nomenclature used on the certificates. Well-documented changes in the smoking habits of doctors may be partly responsible for what appears to have been a relatively favourable experience of ischaemic heart disease from 1947–50 to 1961–5, especially at ages 55–64. Incidence of duodenal ulcer at ages 35–64 declined steadily in this population of doctors from 1947–50 to 1961–5. The decline is very likely to be real.